Prevalence of invasive fungal infection in critically Ill patients: a systematic review and meta-analysis - Mauricio Trelles; José Murillo; Luis Fuenmayor-González; Yunqi Yu-Liu; Harold Alexander-León; Joanna Acebo; Diego Cuicapuza; Marco Morales; Christopher Peña; María Fernanda García-Aguilera (BMC Infectious Diseases)
Abstract Background Invasive fungal infections (IFI) contribute significantly to morbidity and mortality among critically ill patients, particularly in intensive care units (ICUs). Accurate prevalence estimates are essential to inform clinical strategies. This study aimed to determine the prevalence of IFI, and assess regional and methodological variations. Methods A systematic review and meta-analysis were conducted following PRISMA guidelines. Literature from PubMed, Scopus, Web of Science, and Cochrane Library were searched for observational studies published between 1999 and 2024. Inclusion criteria targeted studies reporting IFI prevalence in ICU populations. Data extraction and bias assessment were performed independently by two reviewers. A random-effects meta-analysis assessed pooled prevalence and heterogeneity (Cochran’s Q and I2 statistics). Results Out of 2838 screened articles, 34 studies comprising 655,169 critically ill patients met inclusion criteria. The pooled prevalence of IFI was 5% (95% CI: 3–7%). Aspergillus spp. accounted for 10% and Candida spp. for 3%. Regional prevalence ranged from 3% in high-income countries to 21% in lower-middle-income countries. Diagnostic and methodological heterogeneity were notable contributors to variability. Conclusions IFIs represent a significant burden in ICUs, particularly in resource-limited settings. Standardized diagnostic criteria and region-specific strategies are crucial to improving patient outcomes. Trial registration PROSPERO ID CRD42023472191.